A Nuclear Magnetic Resonance Pulsed Field Gradient study of self-diffusion of water in hydrated cement pastes - Rodin, Victor V.; McDonald, Peter J.; Zamani, Sahar (Diffusion Fundamentals, 2013)
The results of one- and two-dimensional 1H nuclear magnetic resonance (NMR) pulsed field gradient (PFG) diffusometry studies of water in white cement paste with a water-tocement ratio 0.4 and aged from 1 day to 1 year are reported. The study shows that the NMRPFG method is primarily sensitive to the capillary porosity. Data is fit on the basis of a lognormal pore size distribution with pore size dependent relaxation times. The volume mean capillary pore size is 4.2 μm in mature paste, similar to 1 week suggesting that hydrates and gel porosity do not form in the capillary porosity once the latter has been substantially created. No evidence is found of capillary pore anisotropy in cement paste.